Future Skills and Job Architecture for Autonomous Supply Chains (International Journal of Scientific Research in Science and Technology, 2026)
The rapidly evolving Industry 4.0 technologies are shifting the conventional supply chains towards an increasingly autonomous supply chain (ASCs) that possess self learning and self optimizing capabilities coupled with decentralized decision making capabilities. Whilst the technological foundation of autonomy has been extensively researched in the past, little has been deployed as yet regarding the future capabilities and job architecture that would enable it to design, regulate and operate autonomous supply chains in an efficient manner. This is where the article fills this gap by being developed on the synthesis of the autonomous supply chain, Industry 4.0, and logistics and human resource management literature to develop an integrated perspective of the workforce change in autonomous supply chain ecosystems. The paper is based on the conceptual frameworks and the published literature and examines how the supply chain job structure, founded upon the core functions, is changed by the transformation of artificial intelligence, cyber-physical systems, robotics, blockchain and multi-agent architectures to the modified modular, holonic and human-machine structures. The paper goes on to propose a multidimensional future skills model, which would include technical-digital, cognitive-managerial and human-centric skills, which are required to sustain independent functioning. HRM 4.0 implications, reskilling, and industry-specific labor requirements are also discussed in the article and some of the crucial issues are brought up in reference to skills gap, job displacement, and ethical governance. This article can be applied both theoretically and practically in the sense that technology autonomy is linked to technology and design of the workforce to offer strategic recommendations to companies, learning institutions and policy makers interested in developing resilience and humanistic autonomous supply chain.